Plato today - "Crossman, R. H. S" (London, 1959)
To anyone who has ever asked, 'What use is Plato today?' this book is a brilliant reply. It is both an attractive introduction to Greek ideas and also a controversial view of Plato himself. Mr Crossman detests The Republic- 'a handbook for aspiring dictators'-but he knows well its greatness.